2020
DOI: 10.1080/03650340.2020.1807518
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen modulates cotton root morphology by affecting abscisic acid (ABA) and salicylic acid (SA) content

Abstract: A hydroponic experiment was conducted to explore the effects of nitrogen on cotton root morphology and related hormone contents and to analyse the correlation between the indexes. The effects of different nitrogen concentrations (N0, N1, N2, and N3 with 0, 2, 4, and 8 mmol l −1 , respectively) on main and lateral roots were evaluated. A moderate nitrogen concentration (N2, 4 mmol l −1) promotes root growth. Lateral roots responded quickly to changes in nitrogen concentrations. Compared with N0 treatment, N2 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Meanwhile, the root length, root surface area, root volume, root-crown ratio, and biomass of all organs, total N concentrations, and N accumulations of citrus seedlings showed a tendency to first increase and then decrease with the increase of N rates. These were in agreement with the results of previous studies on spruce [55], cotton [56], and passion fruit [57]. The idea was further supported that the root dry weight, root length, and root surface area of rice were increased with an increase of N within a certain range of N applications [58].…”
Section: Effects Of N Application On the Root Morphology Of Citrussupporting
confidence: 92%
“…Meanwhile, the root length, root surface area, root volume, root-crown ratio, and biomass of all organs, total N concentrations, and N accumulations of citrus seedlings showed a tendency to first increase and then decrease with the increase of N rates. These were in agreement with the results of previous studies on spruce [55], cotton [56], and passion fruit [57]. The idea was further supported that the root dry weight, root length, and root surface area of rice were increased with an increase of N within a certain range of N applications [58].…”
Section: Effects Of N Application On the Root Morphology Of Citrussupporting
confidence: 92%
“…Previous studies showed that H 2 O 2 could diffuse through the plant cell membrane and act as a signalling molecule mediating in the early growth during imbibition and germination (Ranieri et al 2020 ), yet the positive effects of PAW in the current study could not be associated with it. In PAWs, NO 3 − and NO 2 − could serve as the source of N and be metabolized by wheat seed, which was the key effector, on the other hand, they could be reduced to NO, which modulated various hormones controlling seed dormancy and germination such as abscisic acid, gibberellins and indoleacetic acid (Chen et al 2020 ; Mu et al 2018 ). And the content of plant nitrogen was closely related to photosynthesis and further affected the accumulation of dry matter in crops (Verkroost and Wassen 2005 ), which explained why wheat seeds exhibited higher mean dry weight and seed vigour when irrigated with PAWs as reported in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it has been found that several plant species link ABA levels with nitrogen status. Although there is considerable evidence of a correlation between ABA levels and nitrogen status in several plant species, the relationship between both is not generally consistent [ 30 , 65 , 82 , 83 , 84 , 85 ]. For instance, there is no statistically significant difference in ABA levels of A. thaliana between high-nitrogen (HN) and low-nitrogen (LN) seedlings [ 86 , 87 ].…”
Section: Abscisic Acid (Aba) Modulates Rsa In Response To Nitrogen St...mentioning
confidence: 99%